Design of fly ash-based alkali-activated mortars, containing waste glass and recycled CDW aggregates, for compressive strength optimization - Miraldo, Sérgio (2022)
Alkali-activated mortars and concretes have been gaining increased attention due to their potential for providing a more sustainable alternative to traditional ordinary Portland cement mixtures. In addition, the inclusion of high volumes of recycled materials in these traditional mortars and concretes has been shown to be particularly challenging. The compositions of the mixtures present in this paper were designed to make use of a hybrid alkali-activation model, as they were mostly composed of class F fly ash and calcium-rich precursors, namely, ordinary Portland cement and calcium hydroxide. Moreover, the viability of the addition of fine milled glass wastes and fine limestone powder, as a source of soluble silicates and as a filler, respectively, was also investigated. The optimization criterium for the design of fly ash-based alkali-activated mortar compositions was the maximization of both the compressive strength and environmental performance of the mortars. With this objective, two stages of optimization were conceived: one in which the inclusion of secondary precursors in ambient-cured mortar samples was implemented and, simultaneously, in which the compositions were tested for the determination of short-term compressive strength and another phase containing a deeper study on the effects of the addition of glass wastes on the compressive strength of mortar samples cured for 24 h at 80 °C and tested up to 28 days of curing. Furthermore, in both stages, the effects (on the compressive strength) of the inclusion of construction and demolition recycled aggregates were also investigated. The results show that a heat-cured fly ash-based mortar containing a 1% glass powder content (in relation to the binder weight) and a 10% replacement of natural aggregate for CDRA may display as much as a 28-day compressive strength of 31.4 MPa.